Implementasi User Acceptance Testing (UAT) Pada Website E-Commerce UMKM BBhealthy - Thabibi, Hilmi; Wati, Seftin Fitri Ana; Rinjeni, Tri Puspa (Mulawarman University, 2025)
Digital transformation within the Micro, Small, and Medium Enterprises (MSMEs) sector plays a vital role in enhancing the dynamics of national economic growth. The impact of this digitalization process is evident through a substantial increase in business revenue and the emergence of new employment opportunities. However, the digitalization process of MSMEs in Indonesia continues to face significant challenges, particularly due to limited digital literacy and technical skills among business owners. This study aims to evaluate user acceptance and satisfaction toward the BBHealthy website as a means of supporting MSME digital transformation. The evaluation was conducted using the User Acceptance Testing (UAT) method to assess the extent to which the developed system meets user needs and expectations. The test results show that the BBHealthy website achieved a final score of 84.6%, which falls within the “Strongly Agree” category (80%–100%). These findings indicate that the system successfully fulfills the operational requirements of an e-commerce business and is well received by its users. This study underscores the importance of user-centered system design in ensuring the successful implementation of digital solutions for MSMEs.